A case study for 3D scanning-based quantitative quality control during key stages of composite small craft production - Dong-Kun Lee; Bon-Yeong Park (International Journal of Naval Architecture and Ocean Engineering, 2023)
Composite small crafts are manufactured in a job-shop system that prioritizes delivery times and creates various small-scale products using flexible equipment and worker operations. The process involves layering composite materials onto a mold to form the product through molding. Three intermediate stages must be completed before the final product, including mock-up, mold, and small craft. The stability and performance of the small craft rely on the accuracy of the mock-up and mold production. However, repeated molding can cause deformation and worker skill level affects product quality, leading to inconsistent results. This study aimed to improve the quality control of composite small crafts in leisure boat shipyards. We propose developing a high-precision digital shape model using 3D scanning of intermediate products such as the ship body frame, finished mold, and shaped hull of the FRP small craft to enable quantitative quality control and identify shape deviations.